Concordance, motivations and associated factors of COVID-19 vaccination among parent–child dyads: a cross-sectional study in Caraga Region, the Philippines - David Jone Lagura Herrera; Deborah Jael Herrera; Krisha Marie Anore; Miraluna Herrera; Anna Lyn A Masing; Ruth E Sanchez; Sherlyn Bas; Donnacham Amora; Renante Pandawatnon Tabudlong; Neamin M Berhe (BMJ Open)
Background COVID-19 vaccination rates remain low for children aged 11 and below, and understanding the extent to which parental decisions impact their children’s vaccination status remains a challenge. This study aimed to explore the concordance and motivations for vaccination among parent–child dyads and determine the associated factors influencing their children’s vaccination status.Design A cross-sectional study was conducted from 1 March 2023 to 30 March 2023, recruiting parents from six representative primary schools across Butuan City, the Philippines. Pilot-tested, self-administered questionnaires were used during the face-to-face surveys with parent participants. To determine the associated factors of parental decisions to vaccinate their children, mixed-effects logistic regression was used, with school districts as a random effect.Participants A total of 593 participating parents were included in the study, with the majority being females (n=484, 81.6%) and underserved, characterised by lacking a college degree (n=305, 51.4%) and having low to no income (n=511, 86.1%).Results While 80.6% (n=478) of parents reported being vaccinated against COVID-19, only 36.2% (n=215) of them chose to vaccinate their children. A significant number of parents (n=285, 48.1%) reported psychological distress, with higher levels of distress prevalent among those who are indigenous, reside in rural areas and have lower income levels. Parental education and vaccination status emerged as influential factors. Specifically, parents with advanced degrees were 48% less likely to have unvaccinated children (adj OR (AOR)=0.52; 95% CI 0.30, 0.87), while unvaccinated parents had a sixfold increase in the likelihood of having unvaccinated children (AOR 6.1; 95% CI 3.14, 12.02) compared with their counterparts.Conclusions Efforts to increase paediatric vaccination rates should focus more on actively engaging parents, educating them about the vaccine’s benefits and necessity, rather than solely relying on mandates to improve paediatric vaccination rates. Further research is needed to understand the reluctance of unvaccinated parents to vaccinate themselves and their children against COVID-19, identifying specific facilitators and barriers to develop more effective communication strategies and bolster vaccine acceptance.